Development of a Problem-Based E-Module on the Immune System Material to Enhance Systemic Thinking Skills - Putri, Denisa Eka; Istiana, Rita; Herawati, Desti; Zahwa, Devalya Khumaila (Journal Of Biology Education Research (JBER), 2025)
One of the major challenges in biology education is students’ limited understanding of abstract and interconnected concepts, particularly in the topic of the immune system, which requires higher order thinking skills. Teacher centered learning and the limited availability of engaging instructional materials often make it difficult for students to recognize the relationships among concepts within a system as a whole. Therefore, innovative learning media are needed to develop students’ systemic thinking skills. This study aims to develop a problem based e-module to enhance students’ systemic thinking abilities on the immune system material. The research employed an R&D approach using the ADDIE model. In the analysis stage, needs assessment was conducted to examine learners’ needs, curriculum requirements, and learning characteristics. The design stage produced an e-module prototype equipped with interactive components such as videos and QR codes. The development stage involved creating the e-module and carrying out validation by content experts, media experts, and language experts. In this study, the development process was limited to the development stage because the primary focus was to produce a learning medium that was judged to be feasible by experts. The validation results indicated that the content experts assessed the e-module as highly feasible for use. The media expert also concluded that the graphical design, content presentation, and language use were categorized as highly feasible. Although media validation was conducted only once, several suggestions for improvement were provided, including adding game based quizzes, embedding hyperlinks to support QR code features, and providing clearer instructions for accessing the embedded learning videos. It can be concluded that the developed e-module is highly feasible for classroom use and is recommended for broader implementation in biology learning.